Peso en Cuyes en engorde con una segunda progenie de cruce genético de tipo absorbente. - Alquinga Ango, Denisse Ivet (2017)
The research project referred to the genetic improvement with the issue of weight in guinea pigs for fattening with a second progeny of genetic crossbreeding of an absorbent type, had the following objectives, to verify the characteristics of guinea pigs selected in the first progeny using parameters of genetic selection in gaining weight; evaluate the improved animals in the second progeny by relating to their weight gain characteristics, relating the weight gain of the guinea pigs in the fattening step of the first and second progeny by comparative analysis assessing the absorbent crossover; The results obtained in the guinea pigs in the fattening stage in the second progeny were according to the selection that was made by the phenotypic characteristics of guinea pigs coloration: red ones and red with white ones and for the presence of swirls, over their heads. This is how the following categories that were red ones with swirl, red ones without swirl, red with white ones painted with swirl and red with white ones without swirl, this characterization allowed us to have groups animals homogeneous, also the weight gain was of the second progeny evaluated in 4 categories, being category 1, red ones. Without swirl with an average gain of weight of 18.86 gr, then category 2 red ones with swirl with an average gain of weight of 17.49 gr, category 3 red with white ones without swirl with a mean weight gain of 16.90 gr, finally category 4 painted with a swirl with a mean of -5.44 g, also showed a positive correlation of (R = 0.07) without analyzing the weight gain between progeny 1 and 2 where progeny 1 in category 1 red ones swirl with a gain of weight of 15 gr, the second category that more the red ones with swirl with a gain of weight of 16,22 gr and in the third category painted without swirl with a gain of weight of 12.05 gr; Unlike progeny 2 where it was evidenced that in the first category there is a weight gain of 16.58 gr, in the red with white ones second category a weight gain of 15.16 gr, and in the third category a weight gain of 17, 78 gr, concluding that the progeny 2 increased the weight gain in category 1 red ones without swirl and category 3 red with white ones without swirl.